Oxidative Stress-Related Parthanatos of Circulating Mononuclear Leukocytes in Heart Failure. (9th November 2017) - Bárány, Tamás; Simon, Andrea; Szabó, Gergő; Benkő, Rita; Mezei, Zsuzsanna; Molnár, Levente; Becker, Dávid; Merkely, Béla; Zima, Endre; Horváth, Eszter M.
Abstract : Background . The present study aims to examine the oxidative stress-related activation of poly(ADP-ribose) polymerase (PARP), a cause of parthanatos in circulating mononuclear leukocytes of patients with chronic heart failure (CHF), that was rarely investigated in the human setting yet. Methods . Patients with CHF (n = 20 ) and age- and body mass index-matched volunteers (n = 15 ) with a normal heart function were enrolled. C-reactive protein, N-terminal probrain-type natriuretic peptide (pro-BNP), plasma total peroxide level (PRX), plasma total antioxidant capacity (TAC), oxidative stress index (OSI), leukocyte lipid peroxidation (4-hydroxynonenal; HNE), protein tyrosine nitration (NT), poly(ADP-ribosyl)ation (PARylation), and apoptosis-inducing factor (AIF) translocation were measured in blood samples of fasting subjects. Results . Plasma PRX, leukocyte HNE, NT, PARylation, and AIF translocation were significantly higher in the heart failure group. Pro-BNP levels in all study subjects showed a significant positive correlation to PRX, OSI, leukocyte HNE, NT, PARylation, and AIF translocation. Ejection fraction negatively correlated with the same parameters. Among HF patients, a positive correlation of pro-BNP with PRX, OSI, and PARylation was still present. Conclusions . Markers of oxidative-nitrative stress, PARP activation, and AIF translocation in blood components showed correlation to reduced cardiac function and the clinical appearance of CHF. These results may reinforce the consideration of PARP inhibition as a potential therapeutic target in CHF.